Health Disparities of Adults with Intellectual Disabilities: What Do We Know? What Do We Do? - Krahn, Gloria L.; Fox, Michael H. (Journal of applied research in intellectual disabilities, 2014)
Background Recent attention to health of people with intellectual disabilities has used a health disparities framework. Building on historical context, the paper summarizes what is known about health disparities from reports and research and provide direction on what to do to reduce these disparities among adults with intellectual disabilities. Methods The present authors examined literature from 2002 to 2011 on health disparities and people with disabilities looking for broad themes on documenting disparities and on research approaches and methods. Results Multiple countries published reports on health of people with intellectual disabilities. Researchers summarized existing research within a health disparities framework. A number of promising methodologies are identified such as health services research, health indicators, enhanced surveillance and mixed‐methods. Conclusions Strategies to reduce health disparities include use of data to educate decision makers, attention to social determinants and a life‐course model and emphasis on leveraging inclusion in mainstream services where possible.